Interpretasi Struktur Bawah Permukaan Menggunakan Data Anomali Medan Magnet Daerah Manifestasi Panas Bumi Sampuraga Kabupaten Mandailing Natal - Tanjung, Rita Ummi Sahida; Pujiastuti, Dwi; Putra, Ardian (Jurnal Fisika Unand, 2023)
This research was conducted to identify the distribution of magnetic field anomalies to determine the subsurface structure of the area around Sampuraga hot springs. Magnetic field data was measured using a magnetometer in an area with dimensions of 1400 m x 1100 m with 154 points. The measurement data is a total magnetic field, and to obtain magnetic field anomaly values, corrections are made for diurnal variation and IGRF correction. Magnetic field anomaly values range from 353,1 nT to 7622,0 nT. Magnetic field anomaly data were processed using the Oasis Montaj software by reducing to the poles, upward continuation, and 2D modeling. The 2D modeling results show three layers of soil in the study area. The upper part (first and second layers) is interpreted as a caprock. This layer consists of sedimentary rock types of sandstone and clay and igneous rock in the form of granite at a depth of up to 1700 m. The lower part (third layer) is interpreted as a reservoir. This layer consists of metasedimentary volcanic rock, clay alteration, andesitic lava, and dacitic lava with a depth of up to 2030 m from the ground surface. The results of this model also interpret the fault zone as an outflow zone so that it forms manifestations on the surface. These three geothermal system components show that the Sampuraga area can be further developed and explored.